PERAN KOMPETENSI AUDITOR ATAS PENGARUH SKALA ENTITAS TERHADAP KUALITAS AUDIT (STUDI BUMN DI BEI) THE ROLE OF AUDITOR COMPETENCE ON THE INFLUENCE ON ENTITY SCALE ON AUDIT QUALITY (STUDY OF SOES ON THE INDONESIA STOCK EXCHANGE) - Pirmansyah, Pirmansyah; Uli. S, Desti Monika; Dewi, Dessy Kumala; Zurman, Zurman; Helmiati, Helmiati (Komunitas Manajemen Kompetitif, 2026)
Audit quality refers to the auditor's proficiency in identifying and disclosing any abnormalities or inconsistencies in the client's accounting information system. The alignment of the audit stages with regulatory regulations (Financial Services Authority and the Ministry of Finance) and the public accountant professional standards (SPAP) is one of the audit quality indicators that can be addressed by auditors. This study aims to provide empirical evidence about the influence of independent variables, namely entity scale on audit quality as a dependent variable moderated by auditor competence. The population in this study is SOEs listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling method used is purposive sampling, based on the criteria obtained by 24 companies as samples with a research period of 5 years so that 120 observation data were obtained. The data was analyzed using moderated regression analysis (MRA). The results of the study stated that the entity scale had a negative effect on audit quality. Auditor competence plays a role in moderating (weakening) the entity scale against audit quality. The contribution of this research is to provide information to shareholders, investors, creditors, and other users of financial statements regarding elements that can affect the quality of audits, thus assisting them in making informed decisions.